Opinions on the Privatization of Distilled-Spirits Sales in Washington State: Did Voters Change Their Minds? - Subbaraman, Meenakshi S. (J Stud Alcohol Drugs, 2016)
OBJECTIVE: In November 2011, voters in Washington State approved Initiative 1183 (I-1183), which ended the government monopoly on distilled-spirits sales. The current study examined the relationship between demographics, spirits use, and voting outcomes, as well as how these variables related to wanting to change one’s vote. METHOD: The sample consisted of 1,202 adults recruited through random-digit-dial methods and reached via telephone between January and April 2014. Bivariate tests and multivariable regressions were used for statistical analyses. RESULTS: Most notably, those who voted Yes on I-1183 had almost eight times the odds of wanting to change their votes compared with those who voted No. Older age, higher education, and being a spirits buyer/drinker were significantly associated with voting (vs. not voting). Among nonvoters, a larger proportion of those who reported that I-1183 was a success (vs. not) were spirits drinkers/nonbuyers. Those who reported that I-1183 was not a success were more likely to report that the number of liquor stores should be decreased. Opinions on taxes were not related to wanting to change one’s vote or thinking that I-1183 had been a success. CONCLUSIONS: The result of the I-1183 election likely would have been different if voters could know their future opinions of the actual situation resulting from privatization. This finding is particularly important for states considering privatization. Results also indicate that spirits drinkers/buyers may be more invested in privatization than nonbuyers and that the increased availability of spirits may affect opinions regarding privatization.